Dose dependent cytotoxic activity of patulin on neuroblastoma, colon and breast cancer cell line - Türkmen, Neşe Başak; Yüce, Hande; Özek, Dilan Aşkın; Aslan, Sümeyye; Yaşar, Şeyma; Ünüvar, Songül (My University, 2021)
Aim: Patulin, a mycotoxin, is an organic compound classified as a polypeptide. Patulin, which is generally detected in moldy fruits and their derivatives, has been suggested to have anticancer activity. Some studies have shown that it induces apoptosis in the cell. This study aims to investigate the anticancer activity of patulin in SH-SY5Y (human neuroblastoma cell line), HCT116 (human colon cancer cell line), and MCF-7 (human breast cancer cell line) cell lines. Materials and Methods: SH-SY5Y, HCT116, MCF-7, and L929 (healthy fibroblast) cell lines were used for cytotoxicity experiments. Cells were added in 96-well plates at 5x103 cells per well. Serial dilutions of patulin at a dose of 1, 2.5, 5, 10, 25, 50, and 100 µM were added to the waiting cells in 24 hours incubation. All cell lines were exposed to patulin for 24 and 48 hours. The cytotoxic activity of patulin in cancer and healthy cell lines was determined in vitro by the MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2- (4-sulphophenyl)-2H-tetrazolium) cell viability test. The results of the toxicity tests were measured spectrophotometrically (450 nm) in ELISA at intervals of 24 hours for 2 days. Results: Patulin caused cytotoxic activity in all cell lines at a concentration of 100 µM. Patulin showed cytotoxic activity at low doses only in the SH-SY5Y cell line. At doses of 25 and 50 µM, HCT116 caused more than 50% death in the cell line, while higher concentrations induced cell death in the MCF-7 cell line. Conclusion: Patulin showed anticancer activity at high concentrations in colon and breast cancer cell lines, and both low and high concentrations in the SH-SY5Y cell line. Patulin may be a new candidate molecule in the treatment of neuroblastoma, colon, and breast cancers, depending on the dose.
Keywords: Onkoloji; Toksikoloji; Biyokimya ve Moleküler Biyoloji